Contagious Effects of Customer Misbehavior in Access-Based Services - Schäfers, Tobias; Wittkowski, Kristina; Benoit (née Moeller), Sabine; Ferraro, Rosellina (Journal of Service Research)
Customer misbehavior in service settings is problematic for two reasons: (1) because of the direct damage it causes and (2) because of additional negative effects that arise from the contagion of such misbehavior. The authors extend existing theory of customer misbehavior by studying its contagious effect. The investigation focuses on access-based services, defined as transactions in which multiple consumers successively gain temporal, short-term access to a good, while legal ownership remains with the service provider (e.g., car sharing and fashion rentals). Due to the nature of these services, they are especially prone to indirect customer misbehavior, which is directed at the accessed product and occurs in the absence of others. Two online experiments provide the first empirical evidence for a contagiousness of misbehavior and reveal that this effect is driven by customers’ perceptions of the social norms among the customer group. Moreover, they indicate that greater strength of the accessed product’s brand as well as lower anonymity of the accessed product’s owner attenuate contagion. A field experiment shows that an increase in the communal identification among access-based service customers reverses the contagious effect, with customers more likely to remove signs of previous users’ misbehavior. The results suggest that access-based service providers should address customer misbehavior by (a) investing in the products they offer access to, (b) establishing more personal relationships with customers, and, foremost, (c) increasing communal identification among customers.